Legal Central Bank Independence and Inflation in Latin America During the 1990s - Jacome, Luis (IMF Working Papers; Working Paper ;, 2001)
This paper reviews central banks' legal reform in Latin America during the 1990s and discusses the status of central bank independence in the region. Based on this information, it builds a simplified index of central bank independence which, in addition to the commonly used criteria of political and economic independence, incorporates provisions of central banks' financial autonomy, accountability, and lender-of-last-resort. The paper finds a moderate negative correlation between increased central bank independence and inflation during 1999-2001 in 14 Latin American countries. Dissagregating the index, the same analysis suggests that economic independence is the key component driving the observed negative correlation between legal central bank independence and inflation.